Dissemination and implementation research in sports and exercise medicine and sports physical therapy: translating evidence to practice and policy - Owoeye, O. B. A.; Rauvola, R. S.; Brownson, R. C. (BMJ Open Sport & Exercise Medicine, 2020)
Knowledge from research evidence is wasted unless it is applied. While the scientific evidence base for many sports and exercise medicine and sports physical therapy interventions is robust, real-world implementation and evolution to scale remains an ongoing challenge. Dissemination and implementation research is important to generate evidence-informed, cost-effective and context-specific strategies for implementation partners and stakeholders to effectively apply and sustain the best research evidence in public health and clinical practice. However, this field of inquiry remains underexplored in sports and exercise medicine and sports physical therapy. Most intervention studies in sports and exercise medicine and sports physical therapy are terminated at the efficacy trial stage without considerations for best practices for translation to community and clinical settings. Lack of context-specific dissemination and implementation strategies to drive the translation of evidence-based interventions results in poor execution of, and attrition from, interventions, and this is associated with suboptimal outcomes and increased healthcare costs. Theory-driven quality research informing the successful dissemination and implementation of evidence-based interventions is needed to address lingering evidence-to-practice gaps. Dissemination and implementation research completes the final stage in the research-to-practice pipeline. It seeks to close evidence-to-practice gaps, thereby ensuring speedy application of research evidence to achieve desired public health outcomes while making more efficient use of limited resources. This review introduces sports and exercise medicine and sports physical therapy researchers and stakeholders to key concepts and principles in dissemination and implementation research.